Gut Microecological Prescription: A Novel Approach to Regulating Intestinal Micro-Ecological Balance - Zhu L; Yang X (International Journal of General Medicine)
Lingping Zhu,1,2 Xuefeng Yang1 1The Affiliated Nanhua Hospital, Department of General Practice, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of China; 2School of Public Health, Fudan University, Shanghai, 200433, People’s Republic of ChinaCorrespondence: Lingping Zhu, Email zlp597@aliyun.comAbstract: The intestinal microecology is comprises intestinal microorganisms and other components constituting the entire ecosystem, presenting characteristics of stability and dynamic balance. Current research reveals intestinal microecological imbalances are related to various diseases. However, fundamental research and clinical applications have not been effectively integrated. Considering the importance and complexity of regulating the intestinal microecological balance, this study provides an overview of the high-risk factors affecting intestinal microecology and detection methods. Moreover, it proposes the definition of intestinal microecological imbalance and the definition, formulation, and outcomes of gut microecological prescription to facilitate its application in clinical practice, thus promoting clinical research on intestinal microecology and improving the quality of life of the population.Keywords: intestinal microecology, risk, gut microecological prescription, definition, faecal microbiota transplantation